2021
DOI: 10.6007/ijarbss/v11-i4/9839
|View full text |Cite
|
Sign up to set email alerts
|

Transcreation Strategies of Male-Related Traits from English Online Fragrance Labels into Chinese: From a Cultural Perspective

Abstract: In recent years, transcreation has been a buzzword in the translation industry and academia. It is defined as a combination of translation and new content creation, with translation used in its traditional sense. Although transcreation strategies have been explored, few studies have addressed whether translation or new content creation predominates in transcreation strategies and the underlying cultural reasons. This study examines the transcreation strategies involved in the Chinese translations of male stere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A recent study on English-language fragrance descriptions (Nemčoková et al, 2021) demonstrated that female stereotypes were generally suppressed, whereas male stereotypes were still present. Further, male stereotypes in fragrance product descriptions have been identified and translated into Chinese (Zhu et al, 2021). However, it remains unknown whether female stereotypes in fragrance product descriptions are imported or manipulated through translation from English (limited to the US websites) into Chinese (limited to mainland China websites).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on English-language fragrance descriptions (Nemčoková et al, 2021) demonstrated that female stereotypes were generally suppressed, whereas male stereotypes were still present. Further, male stereotypes in fragrance product descriptions have been identified and translated into Chinese (Zhu et al, 2021). However, it remains unknown whether female stereotypes in fragrance product descriptions are imported or manipulated through translation from English (limited to the US websites) into Chinese (limited to mainland China websites).…”
Section: Introductionmentioning
confidence: 99%